Pengembangan E-Modul pada Pelajaran Fiqih Bab Haji Kelas X Madrasah Aliyah - Mufidah, Nadia (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
Learning modules are teaching materials that are prepared systematically and interestingly which include material content, methods and evaluations that can be used independently to achieve the expected competencies. Based on initial interviews with Fiqh teachers, information was obtained that there were no modules available on Hajj and Umrah material. Therefore, the resulting module can help students to learn independently. This research aims to find out how the e-module development process in the Hajj chapter Fiqh lesson for the class is valid, effective and practical. This research is research and development that follows the ADDIE development steps. Data collection techniques in research use validation questionnaires, interviews, observation and documentation. The method that will be used is a development method using the ADDIE model which consists of five stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research results show that the learning module developed meets the validity criteria, this was obtained from the results of the validator assessment analysis of 92.44% with the very valid category, at the practicality stage of the module, a percentage of 90.7% was obtained with the very practical category, and at the The effectiveness of the module obtained from the results of the student questionnaire was 89.9% in the very effective category. It can be concluded that the learning module developed meets the criteria of valid, effective and practical.